2022
DOI: 10.3390/biomedicines10092127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Pharmacokinetics to Appraise Adherence to Levetiracetam in Portuguese Epileptic Patients

Abstract: Adherence to antiseizure drug treatment determines its effectiveness and safety, and consequently affects patients’ quality of life. Herein, we assessed adherence to levetiracetam in Portuguese patients with refractory epilepsy (n = 115), with resort to a pharmacokinetic drug monitoring approach. The pharmacokinetic parameters of levetiracetam in each patient were determined in steady-state while admitted to the hospital. Then, adherence was assessed by comparing the plasma concentration of the drug observed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Levetiracetam is an antiepileptic medication indicated as monotherapy in the treatment of partial onset seizures and as adjunct therapy in the treatment of partial onset seizures, monoclinic seizures, and primary generalised tonic-clonic seizures [50]. In a recent study by Silva et al [51], non-adherence to levetiracetam was reported as 42.6% among the study participants.…”
Section: Donepezil Orodispersible Tabletsmentioning
confidence: 99%
“…Levetiracetam is an antiepileptic medication indicated as monotherapy in the treatment of partial onset seizures and as adjunct therapy in the treatment of partial onset seizures, monoclinic seizures, and primary generalised tonic-clonic seizures [50]. In a recent study by Silva et al [51], non-adherence to levetiracetam was reported as 42.6% among the study participants.…”
Section: Donepezil Orodispersible Tabletsmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) is an essential tool to address this complexity, enabling the definition of individual therapeutic concentrations and adaptive control of dosing to minimize drug interactions and prevent loss of efficacy or toxicity (Krasowski, 2010). Some studies have shown that PER plasma levels were affected by otherAEDs in routine TDM practice, including carbamazepine, phenobarbital, valproate and topiramate (Patsalos et al, 2016;Contin et al, 2018;Silva et al, 2023). A recent study indicated that enzyme-inductive AED could increase PER clearance (Fujita et al, 2022).…”
Section: Introductionmentioning
confidence: 99%